Computational study of elastic and inelastic ring shaped – steel plate shear wall behavior. (15th December 2018) - Phillips, Adam R.; Eatherton, Matthew R.
Highlights: Finite element models of RS-SPSWs were validated against experimental hysteretic behavior. A Cinner = 0.3 can be used to predict the deformation demand on the outer rings. An elastic analysis can be used to calculate RS-SPSW boundary element forces. RS-SPSW are more resistant to shear buckling than solid steel plate shear walls. RS-SPSW web slenderness should be limited to 190 to prevent elastic shear buckling. Abstract: Ring shaped – steel plate shear walls (RS-SPSWs) are a new type of steel plate shear wall (SPSW) system that utilize strategic cutouts in a solid plate to mitigate shear buckling and encourage full hysteretic behavior and thus large energy dissipation. Previous experiments have demonstrated that the RS-SPSW concept can significantly reduce buckling and dissipate more energy than solid web plate SPSWs with similar strength. However, because of limitations in the number of tests and associated instrumentation, the experimental results did not provide enough data to thoroughly investigate several facets of RS-SPSW behavior, such as the distribution of shear deformation along the web plate height, web plate forces on the boundary elements, and web plate slenderness effects on buckling resistance. This paper details three computational studies that build upon the experimental test results to develop and validate useful design equations for RS-SPSWs. The paper starts with a description of the RS-SPSW nonlinear finite element models that utilize shell elements for the web plate. Then, the model is validated against experimental specimens by comparing the load-deformation behavior and the evolution of cumulative energy dissipation. Next, the computational models are utilized to explore the uneven shear deformation distribution along the height of the web plate allowing derived prediction equations to be validated. The computational models are also used to determine boundary element demands and to validate a proposed distribution of web plate forces for use in design. Lastly, the modeling approach is utilized to better understand shear buckling of the web plates in terms of non-dimensional web plate parameters.